P4.096 Sexual Network and Practise of Female Sex Workers in Sikkim. (13th July 2013) - Chowdhury, S; Panda, N; Kundu, M; Basu, R; Sonkar, R; Konar, S Das; RoyChoudhury, A
Abstract : The problem: 'Sikkim is an orthodox state in India. It has a traditional society which believes that polygamy does not exist. There was no authentic study to validate the statement. According to the estimate of 2007, prevalence rate of HIV was 0.6.Though Sikkim SACS is running Targeted Intervention programme, the target population is a hidden one and no penetration is happening by TI' (Valla A, 2006). A study was conducted on socio sexual network and practise of Female Sex Workers (FSWs) in collaboration with Sikkim SACS in the month of Nov, 2012. Methodology: Sample size was 70 selected through Stratified random sampling (10% of the total population registered under NGO programmes of Sikkim SACS) Result and discussion: 70% of respondent is engaged in sex work along with other profession while 30% is dependent solely in sex work profession. 88% of respondent is coming to sex work profession for economic reason. Among this 88%, 65% is working for less than 1 year. 70% of respondent work more than 20 days a month having an average of 30 partners. 80% of respondent are below age 25 yrs who have more than 30 sexual partners -i.e. less age group is more vulnerable. 80% of the respondent consumed alcohol. Among 70% of alcohol users, 90% is not using condom.10% of the respondent taking drug through injecting route. 90% of respondents have heard of HIV while 30% of them have accessed TI services.10% of respondent explained about STI sign & symptoms whereas the prevalence rate is 70%. Conclusion: The study shows that polygamy exists in the state and an emerging trend of new FSW noticed. Condom use, knowledge of STI and HIV both are low. The national control programme should develop Sikkim specific design to address these issues.